Effects of rarity form on species' responses to land use. Issue 3 (29th November 2019) - Sykes, Louise; Santini, Luca; Etard, Adrienne; Newbold, Tim
Abstract: Anthropogenic land‐use change causes substantial changes in local and global biodiversity. Rare and common species can differ in sensitivity to land‐use change; rare species are expected to be affected more negatively. Rarity may be defined in terms of geographic range size, population density, or breadth of habitat requirements. How these 3 forms of rarity interact in determining global responses to land use is yet to be assessed. Using global data representing 912 vertebrate species, we tested for differences in responses to land use of species characterized by different types of rarity. Land‐use responses were fitted using generalized linear mixed‐effects models, allowing responses to vary among groups of species with different forms of rarity. Species considered rare with respect to all 3 forms of rarity showed particularly strong declines in disturbed land uses (>40% of species and 30% of individuals in the most disturbed land uses). In contrast, species common both geographically and numerically and with broad habitat requirements showed strong increases (up to 90% increase in species and 40% in abundance in some land uses). Our results suggest that efforts to understand the vulnerability of species to environmental changes should account for different types of rarity where possible. Our results also have potentially important implications for ecosystem functioning, given that rare species may play unique roles within ecosystems. Abstract : Article impact statement : Rare species show stronger negative responses to anthropogenic land use than common species. Abstract : Efectos de la Forma de Rareza sobre las Respuestas de las Especies ante el Uso de Suelo Sykes et al. Resumen: Los cambios en el uso de suelo ocasionados por el humano causan modificaciones sustanciales en la biodiversidad local y mundial. Las especies raras y comunes pueden tener diferencias en la sensibilidad ante el cambio en el uso de suelo; generalmente se espera que las especcies raras se vean afectadas de manera más negativa. La rareza puede estar definida en términos del tamaño de la extensión geográfica, la densidad poblacional o la gama de requerimientos de hábitat. La manera en que interactúan estas tres formas de rareza para determinar las respuestas mundiales ante el uso de suelo todavía no ha sido evaluada. Buscamos diferencias en las respuestas ante el uso de suelo en especies caracterizadas por diferentes tipos de rareza. Para esto usamos datos mundiales que representaron a 912 especies de vertebrados. Las respuestas ante el uso de suelo fueron ajustadas con modelos lineales y generalizados de efectos mixtos, lo que permitió que las respuestas variaran entre los grupos de especies con diferentes formas de rareza. Las especies consideradas como raras con respecto a las tres formas de rareza mostraron declinaciones particularmente fuertes en los usos de suelos perturbados (>40% de las especies y 30% de los individuos en los usos de suelo más perturbados). Como contraste, las especies comunes tanto geográfica como numéricamente y con requerimientos amplios de hábitat mostraron incrementos sólidos (hasta un 90% de incremento de las especies y 40% en abundancia para algunos usos de suelo). Nuestros resultados sugieren que los esfuerzos para entender la vulnerabilidad de las especies ante los cambios ambientales deberían considerar los diferentes tipos de rareza cuando sea posible. Nuestros resultados también tienen implicaciones potencialmente importantes para el funcionamiento de los ecosistemas, dado que las especies raras pueden tener un papel único dentro del ecosistema. 摘要: 人类导致的土地利用变化对局部和全球生物多样性造成了重大影响。稀有种和常见种在对土地利用变化的敏感性上有所不同; 稀有种可能会遭受更多负面影响。物种的稀有性可以根据地理范围大小、种群密度和生境需求宽度三个方面来界定。然而, 这三个方面的稀有性在决定全球范围内物种响应土地利用中如何相互作用仍有待评估。我们利用全球 912 种脊椎动物的数据, 检验了不同类型的稀有种对土地利用响应的差异。其中, 物种对土地利用的响应由广义线性混合效应模型来拟合, 允许响应在不同类型稀有种的组间变化。三个方面都稀有的物种在受干扰土地利用类型中表现出急剧下降 (受干扰最严重的土地利用类型中超过 40% 的物种和 30% 的个体数量下降) 。相比之下, 在地理分布、种群数量和生境需求宽度上都属于常见种的物种则表现出大幅增长 (一些土地利用类型中物种数增长达 90%, 丰度增长达 40%) 。我们的研究结果表明, 在理解物种面对环境变化的脆弱性时, 应尽可能考虑不同类型的稀有物种。鉴于稀有种在生态系统中可能具有独特的作用, 我们的结果对生态系统功能研究也有潜在的重要意义。【翻译: 胡怡思; 审校: 聂永刚】